Implementation of Finite Element Method for Structural Analysis of Bridge Resistance - Erwin,; Joni, Joni; Marpaung, Jonathan Liviera (Journal of Research in Mathematics Trends and Technology, 2021)
The bridge problem is on of the structural phenomenon in physical structural analysis. One of the problems of bridge is how to analyze the fatigue of bridge model so that the the resistance of the bridge may be estimate. In this paper the bridge problem will be explained using Finite Element Method in displacement function analysis. The stress-strain number will be written in parameters of bridge model. the displacement function is clearly influenced by the stress-strain value so that the initialization of the initial value will follow the value of the specified parameter. In this paper the displacement function of the bridge will be explained in simulation model. The result of this research is the difference about initial model to the simulation model so that the resistance of the model can be analyze caused of the initial parameters.